Cobalt nanoparticles supported on microporous nitrogen-doped carbon for an efficient catalytic transfer hydrogenation reaction between nitroarenes and N-heterocycles. Issue 18 (12th August 2022) - Lu, Xiaomei; Qin, Jingzhong; Xian, Chensheng; Nie, Jiabao; Li, Xun; He, Jie; Liu, Bing
Abstract : Cobalt nanoparticles supported on microporous nitrogen-doped carbon (Co/mNC) were prepared for catalytic hydrogen transfer between nitroarenes and N-heterocycles. Abstract : A catalytic transfer hydrogenation reaction between nitroarenes and saturated N-heterocycles to simultaneously synthesize value-added anilines and unsaturated N-heterocycles is attractive due to its low-cost, atom economic, and environmental-friendly properties. Herein, we report cobalt-based catalysts prepared via a simple pyrolysis method, namely cobalt nanoparticles supported on microporous nitrogen-doped carbon (Co/mNC). The optimized catalyst (Co/mNC-500) showed excellent performance towards the catalytic transfer hydrogenation reaction between nitrobenzene and 1, 2, 3, 4-tetrahydroquinoline, yielding more than 90% aniline and quinoline after a 24 hour reaction. Moreover, this catalytic system was available to a wide scope of substrates, and thus a variety of anilines as well as quinolines, isoquinolines, and indoles could be synthesized in great yields. Characterization and control experiments revealed that Co nanoparticles (Co NPs) were the dominant cobalt species evenly distributed on the microporous nitrogen-doped carbon support, serving as the reaction active centres. Based on the experimental results, a plausible reaction mechanism was proposed, in which Co NPs played an essential hydrogen abstraction and delivery role during the catalytic transfer hydrogenation process.